1998
DOI: 10.1182/blood.v92.9.3025
|View full text |Cite
|
Sign up to set email alerts
|

The t(4;14) Translocation in Myeloma Dysregulates Both FGFR3and a Novel Gene, MMSET, Resulting in IgH/MMSET Hybrid Transcripts

Abstract: Previously we reported that a karyotypically silent t(4;14)(p16.3;q32.3) translocation is present in about 25% of multiple myeloma (MM) tumors, and causes overexpression of FGFR3, which is 50 to 100 kb telomeric to the 4p16 breakpoints. Frequent FGFR3 kinase activating mutations in MM with t(4;14) translocations substantiate an oncogenic role for FGFR3. We now report that the 4p16 breakpoints occur telomeric to and within the 5′ introns of a novel gene,MMSET (Multiple Myeloma SETdomain). In normal tissues, MMS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
197
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 478 publications
(201 citation statements)
references
References 30 publications
4
197
0
Order By: Relevance
“…Multiple myeloma (MM) is a malignancy of bone marrow plasma B cells (1), and despite extensive study, its etiology remains unclear. The t(4;14)(p16.3:q32.3) chromosomal translocation is detected in ;20% of MM cases and is associated with a worse prognosis (1,2). The t(4;14) translocation transposes the immunoglobulin heavy chain region enhancer on chromosome 4 and the Wolf-Hirschhorn syndrome candidate 1 (WHSC1), multiple myeloma set domain (MMSET) gene on chromosome 14 (2), resulting in the ectopic overexpression of the WHSC1 and FGFR3 genes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple myeloma (MM) is a malignancy of bone marrow plasma B cells (1), and despite extensive study, its etiology remains unclear. The t(4;14)(p16.3:q32.3) chromosomal translocation is detected in ;20% of MM cases and is associated with a worse prognosis (1,2). The t(4;14) translocation transposes the immunoglobulin heavy chain region enhancer on chromosome 4 and the Wolf-Hirschhorn syndrome candidate 1 (WHSC1), multiple myeloma set domain (MMSET) gene on chromosome 14 (2), resulting in the ectopic overexpression of the WHSC1 and FGFR3 genes.…”
mentioning
confidence: 99%
“…The t(4;14)(p16.3:q32.3) chromosomal translocation is detected in ;20% of MM cases and is associated with a worse prognosis (1,2). The t(4;14) translocation transposes the immunoglobulin heavy chain region enhancer on chromosome 4 and the Wolf-Hirschhorn syndrome candidate 1 (WHSC1), multiple myeloma set domain (MMSET) gene on chromosome 14 (2), resulting in the ectopic overexpression of the WHSC1 and FGFR3 genes. Where FGFR3 is deleted in a subset of t(4;14) cases that still have a poor prognosis (3), all cases of t(4;14) myeloma overexpress the MMSET gene, which encodes a H3K36 histone methyltransferase.…”
mentioning
confidence: 99%
“…MMSET is a 90 kb gene with 24 exons having a complex expression pattern caused by alternative splicing and differential polyadenylation (Chesi et al, 1998). The MMSET mRNA isotypes include MMSET type I encoding a shorter protein (647 aa) and MMSET type II encoding a longer protein (1365 aa) ( Fig 1B).…”
mentioning
confidence: 99%
“…Recently, a third mRNA isotype (RE-IIBP) has been found that encodes a 584 aa protein identical to the carboxy-teminal region of MMSET type II (Garlisi et al, 2001) ( Fig 1B). MMSET is highly expressed in testis and thymus in adult tissues and to a high degree in embryonic tissues, especially those undergoing rapid proliferation (Chesi et al, 1998). However, the MMSET proteins remain to be identified.…”
mentioning
confidence: 99%
See 1 more Smart Citation